A high‐efficiency DOPO‐based reactive flame retardant with bi‐hydroxyl for low‐flammability epoxy resin. Issue 14 (27th October 2020) - Zhang, Junjun; Duan, Huajun; Cao, Jianfan; Zou, Jiahao; Ma, Huiru
Abstract: A high‐efficiency DOPO‐based reactive flame retardant (DPE) with bi‐hydroxyl was successfully synthesized via reacting DOPO with imine obtained from the condensation of ethanolamine and 1, 4‐phthalaldehyde, and used as co‐curing agent to improve the fire safety of epoxy resin (EP). Its chemical structure was characterized by Fourier transform infrared (FTIR) spectra, 1 H, 31 P nuclear magnetic resonance (NMR) spectra and elemental analysis. The curing behavior, thermal properties, flame‐retardant properties of EP/DPE systems were investigated. The results revealed that DPE slightly decreased the glass transition temperature ( T g ), but accelerated the curing cross‐linking reaction of EP. Furthermore, DPE decreased thermal degradation rate of epoxy matrix and promoted the formation of residual char at high temperature. After adding DPE, the flame retardant of epoxy thermosets was greatly improved. Especially, the thermoset modified with 5 wt% DPE achieved limiting oxygen index (LOI) value of 33.6% and V‐0 rating in UL‐94 test, demonstrating the highly efficient flame retardancy. While its peak heat release rate (PHRR), total heat release (THR) and total smoke production (TSP) were respectively decreased by 32.6%, 17.8%, and 13.9% compared with neat EP. Moreover, the research on flame retardant mechanism disclosed that DPE played dual flame‐retardant effect in the gaseous and condensed phases. Abstract : A DOPO‐based flame retardant co‐curing agent with bi‐hydroxyl was prepared. DPE was highly efficient in improving the fire safety of EP. DPE accelerated the curing cross‐linking reaction of EP. DPE exerted dual flame‐retardant effect both in the gaseous and condensed phases. The cured EP maintains its transparency.